pistis christu The Current State of Play and the Key Arguments - Kugler, Chris (2016)
The pistis Christou debate involves numerous debate partners and a shockingly voluminous amount of secondary literature. At this point, I thought it necessary to provide a survey of the current state of the debate, not least so as to summarize in one place the main arguments for both sides of the debate. At the beginning of the article I gather together and present the main arguments for those advocating an objective reading of the phrase, while the second half of the essay mainly involves a presentation of the arguments for the subjective camp. Having provided this summary, with many comments of my own alongside, I conclude by emphasizing the two pieces of evidence that seem still to push in the direction of the subjective construal. When the survey comes to a close, I arrive at the conclusion that, while debate is certainly not over, those advocating a subjective reading of the expression have the momentum of the scholarly guild.
Keywords: Faith; Faithfulness; Galatians; Habakkuk; Literature; Objective; Paul; Pistis Christou; Reading; Revelation; Righteousness; Romans; Subjective